The impact of rheumatic diseases in Iraq on pregnant women whose ages range from (25-35 years) - Dr. Ruaa Abdulelah Mohammed Oleiwi; Dr. Nibras Shaheed Noori; Dr. Rasha Abdul-Ridha Musa (Zien Journals, 2023)
Rheumatoid arthritis (RA) is a chronic, recurrent inflammatory autoimmune condition characterized by persistent inflammation of the synovial joints, which over time and especially without intensive treatment, leads to erosive development, with the destruction of the articular cartilage and complete loss of joint integrity
Keywords: Rheumatoid arthritis; Juvenile idiopathic arthritis; Psoriatic arthritis